Few‐Layer Tin Sulfide: A Promising Black‐Phosphorus‐Analogue 2D Material with Exceptionally Large Nonlinear Optical Response, High Stability, and Applications in All‐Optical Switching and Wavelength Conversion. Issue 2 (19th December 2017) - Wu, Leiming; Xie, Zhongjian; Lu, Lu; Zhao, Jinlai; Wang, Yunzheng; Jiang, Xiantao; Ge, Yanqi; Zhang, Feng; Lu, Shunbin; Guo, Zhinan; Liu, Jie; Xiang, Yuanjiang; et al.
Abstract: As an analogue compound of black phosphorus, a new 2D semiconducting few‐layer SnS is successfully synthesized, and its nonlinear optical response is investigated. It is shown that its nonlinear refractive index and third‐order nonlinear susceptibility are measured as n 2 ≈ 10 −5 (cm 2 W −1 ) and χ monolayer ( 3 ) ≈ 10 −10 (e.s.u.), respectively. By taking advantage of such a large Kerr nonlinearity, an all‐optical switching technique based on few‐layer SnS is realized through modulating the propagation of the signal beam by another controlling beam. The achievement of all‐optical switching indicates that few‐layer SnS could be developed as an excellent optical material for all‐optical signal processing. More importantly, a conceptually new and reliable information conversion system based on spatial cross‐phase modulation in few‐layer SnS, that is, the transmission and conversion of a sequence of bit information from one wavelength channel to the other, is presented. The contributions reveal potential applications of few‐layer SnS as a new type of optical information material, and it is therefore anticipated that SnS and other IV–VI compound‐based 2D nanomaterials could find promising applications in photonic devices such as optical modulators, optical switches, detectors, etc. Abstract : By taking advantage of the Kerr nonlinearity, an all‐optical switching technique based on few‐layer SnS is realized through modulating the propagation of the signal beam by another controlling beam. The achievement of all‐optical switching indicates that few‐layer SnS could be developed as an excellent optical material for all‐optical signal processing.